Cobalt-catalyzed nucleophilic addition of the allylic C(sp3)–H bond of simple alkenes to ketones - Mita, Tsuyoshi; Uchiyama, Masashi; Michigami, Kenichi; Sato, Yoshihiro (Beilstein Journal of Organic Chemistry, 2018)
We herein describe a cobalt/Xantphos-catalyzed regioselective addition of simple alkenes to acetophenone derivatives, affording branched homoallylic alcohols in high yields with perfect branch selectivities. The intermediate of the reaction would be a nucleophilic allylcobalt(I) species generated via cleavage of the low reactive allylic C(sp3)–H bond of simple terminal alkenes.
Keywords: alkenes; C–H activation; C(sp3)–H bonds; cobalt; ketones